Aktualisasi Misi Penginjilan Melalui Guru Pak dalam Mendewasakan Iman Peserta Didik - Des Samuel Randi Pasaribu; Deva Kusrini Br Manik; Josua Siburian; Riris Simatupang; Oloria Malau (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
Professionalism is a word that is often used when we see someone who has great skills, or someone who is an expert in their field, has reliable skills, and is responsible for their work. By working professionally, a teacher can be trusted in terms of teaching and so on, so that he can become a quality teacher, so that the teacher can be seen as someone who has a noble profession. Christian teachers play a very important role in determining the spiritual growth of their students, but many still fail to recognize and respond to the reality of turbulent times. Children's Christian religious education is the most important thing in their lives. Serving a mission to reach children, Christian Religious Education provides an approach to children, where Christian Religious Education has a concept that focuses on how to educate them. The role of teachers in the mission of Christian Religious Education must be a top priority. One of the main goals is to shape or provide direction to the participants. Educate about their faith and spiritual development. Therefore, in this case the author uses descriptive qualitative methods so that the meaning of the research results can be understood.